Prognostic Value of NT-proBNP in Predicting Adverse In-hospital Outcomes among Patients of STEMI getting Thrombolytic therapy without Clinical Manifestation of Heart Failure - Dutta, Bijoy; Mohibullah, AKM; Karmoker, Kajal Kumar; Siddique, Khandaker Ayesha; Chowdhury, Sanjib; Kundu, Samir Kumar; Rahman, Zillur; Roy, Dipankar (Cardiovascular Journal, 2017)
Background: Risk stratification is extremely important in ACS patients especially acute STEMI. We studied in-hospital outcomes of acute STEMI according to their NT-proBNP level as a new prognostic marker. Methods: This observational prospective study was conducted to evaluate the significance of raised plasma NT-proBNP level on in-hospital outcomes in patients with STEMI, without clinical manifestation of heart failure. A total 88 patients of STEMI were included in the study. Among them 10 Patients have normal levels of NT-proBNP (<110 pg/ml) and were included in Group-A (n = 10). Patients with increased proBNP level (e110 pg/ml) were included in Group-B (n = 78). Patients were followed to see worse in-hospital outcomes (Heart failure, cardiogenic shock, significant arrhythmia and death) during index hospitalization period. Results: Plasma NT-proBNP level was observed to be significantly higher among patients who developed heart failure, cardiogenic shock and death than the patients who did not developed these outcome (p < 0.001). The binary logistic regression analysis of Odds Ratios for characteristics of the patients likely to cause worse in-hospital outcome shows that NT-ProBNP and smoking habit were found to be the independent predictors of worse in-hospital outcome with ORs being 5.0 and 4.7 respectively. Conclusion: On admission plasma NT-pro BNP level in patients with STEMI is a strong independent predictor of adverse in-hospital outcome. Cardiovasc. j. 2017; 10(1): 8-12